Epstein–Barr virus in pleural effusions: protagonist or pretender?. Issue 4 (31st October 2019) - Arnold, David T.; Suri, Tim; Hamilton, Fergus; Morley, Anna; Medford, Andrew; Vipond, Ian B.; Muir, Peter; Maskell, Nick A.
Unilateral pleural effusions are a common diagnostic challenge for the respiratory physician. In the majority of patients, a diagnosis can be made according to medical history, computed tomography and pleural fluid analysis [1]. A proportion of patients will require a pleural biopsy but, following this, a minority will remain undiagnosed and are defined as having inflammatory pleuritis (IP) [2]. These patients often require extended follow-up to ensure effusion resolution and exclude malignancy. Previous studies have suggested an association between Epstein–Barr virus (EBV) and inflammatory pleuritis (IP). The incidence of IP in this 1005-patient cohort was 3%, with no evidence of increased pleural fluid EBV DNA compared to controls. http://bit.ly/2lVGvNV